Optimization and simulation of secondary settler models - Espírito Santo, I. A. C. P. (2006)
This work focus on the accomplishing of the best model to a secondary settler to use in a minimum cost optimization procedure concerning the construction and operation of a wastewater treatment plant (WWTP). Two traditional models are tested as well as a new model that results from the combination of the other two. The obtained optimal designs are then simulated in order to evaluate the model that provides the best performance.